International Relations Theory and World Order: Binaries, Silences and Alternatives. (March 2014) - Srivastava, Jayati; Sharma, Ananya
Mainstream international relations theory is consumed by its proclivity towards order; the genesis of which has been attributed to its statist ontology. Such theorisations, by drawing binaries between order and disorder, either assume or normalise order or obfuscate and suggest ways of mitigating any kind of disorder. Paradoxically, questions about the foundational edifice of order are marked by silences. Within the context of world order, this obtains a theoretical framework that precludes any normative reflection on the making and unmaking of world order or the principles that sustain that order. The article looks at how different branches of international relations theory envisage world order and the silences embedded therein. Further, by locating order and disorder inhabiting the same reality along a continuum, alternative readings of world orders are drawn from the critical theoretical traditions in which various articulations of justice impart normative pillars to the world order.